Star formation and disk stability in nearby galaxies - Naluminsa, Elizabeth (Department of Astronomy, 2019)
Observations of apparent cutoffs in star formation in the disks of galaxies as well as apparent thresholds in empirical laws of star formation have led many workers in the field to seek out the drivers and regulators of star formation in galaxies. Although the intricate details of these drivers are yet to be untangled, one of the main theories put forward is the existence of a gravitational stability threshold, controlled by the balance between the pressure-forces and gravity in a galactic disk to determine where gas collapses to form stars. Studies on this have mainly focused on the radial variation of the gravitational stability parameter and how it relates to the radial variations in the star formation activity. In this study, we look at the two dimensional structure of this parameter across the disks of star forming galaxies and compare it with the two dimensional structure of the star formation activity. The gravitational stability of the disks was derived using two different models. (i) The thin gas-disk model (single-fluid disk criterion, Qg) was derived for each galaxy in our sample. We use atomic gas for the majority of the sample and we use molecular gas whenever available. (ii) A two-fluid disk criterion which models a galaxy disk with gas and stars as two distinct fluids each with single-fluid instabilities and together having the combined twofluid instabilities (QT ). Both models were compared to maps of star formation rate. Data from the Westerbork survey of Hi in Irregular and SPiral galaxies (WHISP) were used to trace the properties of the gas disk, while data from the Wide-field Infrared Survey Explorer (WISE) were used to derive the stellar disk and star formation properties. In the case of the single-fluid thin gas-disk model, we find that the star forming disks show typical values of 3 - 15, much higher than the theoretical threshold value of 1. The high values can be attributed to low Hi gas densities (ΣHi) in the central regions, although the general structure in the maps traces the local density enhancements. However, the structural variations in Qg do not correlate with local variations in the surface density of the star formation rate, except in 25% of the sample, which are late type and have high gas fractions relative to the rest of the sample. This result confirms previous findings of 1D studies that the single-fluid criterion is better suited for late type galaxies. This is because the low stellar surface densities coupled with high gas fractions make the thin gas disk approximation yield a close description of late types. In addition to the above, we find that the values of Qg along the edges of the star forming disks are generally lower than those inside the disk. In about half the sample, the values on the edges are found to be roughly constant with an overall average of 4.0, which is four times higher than the theoretical threshold but in agreement with previous studies of the radial variation of Qg. Incorporating the stellar disk (the two-fluid disk criterion) leads to lower stability for all the disks in the sample, which is consistent with the increased gravity budget of the disks. Nevertheless, the two-fluid consideration does not render the disks unstable. In fact, we see that 80% of the galaxies in the sample have QT ≈ 2 or higher. The QT values vary only slightly, yielding flat maps consistent with previous studies of the azimuthally-averaged QT parameter. The overall average value of QT is 2.5 both inside the star forming disks and at the edges. This is in agreement with previous studies which showed that the critical value of the two-fluid disk criterion lies between 2 - 3. In spite of the mostly flat featureless QT disks, four galaxies had some variations in QT across their disks which mapped lower stability values to local regions of enhanced star formation. It is interesting to note that these galaxies also had lower Qg values matching the locally enhanced SF regions, although the QT maps had lower stability values and more extended patches. All four galaxies are late types. This confirms previous findings that the single-fluid disk criterion may be a reliable predictor of star formation in late type galaxies. This is because the stellar surface density in late types is low, and if coupled with a high gas fraction as is the case for these four galaxies, the gas-disk predictions will be close to the predictions for a disk of gas+stars. Additionally, as part of characterization of our sample, we have also studied the scaling relations between atomic gas and star formation rate. We found general correlation between the the star formation rate and Hi surface densities on sub-kpc scales, defined by a non-linear power law relationship with index varying between 1.6 - 3.8.